Preterm birth and stillbirth during COVID-19 pandemic in Bihor County/Romania - Radu Galis; Radu Galis; Paula Trif; Paula Trif; Diana Mudura; Romina Murvai; Romina Murvai; Lucia Georgeta Daina; Florin Szasz; Florin Szasz; Rodica Negrini; Adrian Hatos; et al. (Frontiers in Reproductive Health, 2024)
BackgroundInternational studies have reported conflicting data about the effects of COVID-19 pandemic policy measures on maternal and neonatal health. A major impact was reported on stillbirth and prematurity. The published literature suggests that the economic setting influenced the effects of imposed mitigation measures with a more severe effect in low-income countries.ObjectivesOur objective is to compare pregnancy outcomes at the only tertiary Maternity Hospital in Bihor County-Romania before and during the COVID-19 pandemic. This study aims to observe and document differences in perinatal outcomes across these periods, without inferring direct causation related to the pandemic or its associated restrictions.Materials and methodsWe used data from the registries of Public Health Services Bihor to conduct a retrospective cohort analysis of preterm births and stillbirths during the COVID-19 pandemic in Bihor County, Romania. Pregnancy outcomes were compared between the pandemic period (March 2020–February 2022) to the corresponding historical pre-COVID-19 period (March 2018–February 2020). Maternal socio-demographic variables and neonatal characteristics of these periods were also examined.ResultsThe COVID-19 pandemic period was associated with an increase in the stillbirth rate (RR: 1.53, 95% CI, 1.05–2.23). Preterm birth was significantly impacted during this period and showed changes when analyzing gestational age (RR: 0.88, 95% CI, 0.79–0.96) or birth weight (RR: 0.91, 95% CI, 0.82–1.00). The main cause of stillbirth was intrauterine asphyxia due to placental causes (67.6%) or cord pathology (12.6%), the most frequently encountered maternal pathology was cardiovascular (28.3%) or infectious (21.7%). Our study revealed no significant changes in terms of maternal and neonatal characteristics during the two-year pandemic period.ConclusionsLockdown restrictions in Bihor County, Romania were associated with an increase in stillbirths, whilst preterm birth rate decreased. This raises concerns about whether pandemic policy measures may have led to a failure in identifying and offering proper care for pregnant women who were more likely to experience an antepartum loss. Further studies across the globe are needed in order to integrate comparable data that will help develop adequate protocols and policies for protecting maternal and child health during the next pandemic that will follow.